Volumetric assessment of individual thalamic nuclei in patients with drug-naïve, first-episode major depressive disorder - Chibaatar, Enkhmurun; Watanabe, Keita; Okamoto, Naomichi; Orkhonselenge, Nasanbadrakh; Natsuyama, Tomoya; Hayakawa, Gaku; Ikenouchi, Atsuko; Kakeda, Shingo; Yoshimura, Reiji (Frontiers in Psychiatry, 2023)
Introduction Despite the previous inconsistent findings of structural and functional abnormalities of the thalamus in patients with major depressive disorder (MDD), the disruption of the thalamic nuclei in the pathophysiology of this disorder has not yet been adequately studied. Therefore, we investigated the volumetric changes of thalamic subregions and their nuclei in drug-naïve, first-episode MDD patients. We also investigated the association between HAM-D scores, a clinical scale frequently used to evaluate the severity of depression and thalamic nuclei volumes in MDD patients. Methods This study included 76 drug-naïve MDD patients and an equal number of healthy subjects. Magnetic resonance imaging (MRI) data were obtained using a 3T MR system and thalamic nuclei volumes were evaluated using FreeSurfer ver.7.11. The volumetric differences were compared by one-way analysis of covariance (ANCOVA) and to ensure that effects were not accounted for by other factors, age, sex, and ETICV variables were included as covariates. Results We observed significant volume reductions of the left whole thalamus (p < 0.003) and several thalamic nuclei mostly on the left side in the MDD group compared with healthy controls (HCs). Furthermore, we have revealed weak negative correlations between several thalamic nuclei volumes and HAM-D total and subscale scores. Discussion This is the first research study to investigate alterations of the various thalamic nuclei volumes in MDD patients compared with HCs. Moreover, we first analyzed the association between individual thalamic nuclei volumes and HAM-D subscale scores. Though our study may be restricted at certain levels, especially by the demographic difference between the two groups, they possibly contribute at a preliminary level to understanding the thalamic structural changes at its subregions in patients with drug-naïve, first-episode MDD.